BRAND IMAGE, CUSTOMER EXPERIENCE, VANITY SEEKING, MATERIALISM TERHADAP CUSTOMER LOYALTY DAN REPURCHASE INTENTION - Srinandari, Putu Riska Yunita; Sunariani, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.03.TAHUN.2022DO - 10.24843/EEB.2022.v11.i03.p04, 2022)
This study aims to analyze Brand Image, Customer Experience, Vanity Seeking, Materialism on Customer Loyalty and Repurchase Intention. This research is included in quantitative research and was conducted at Larissa Aesthetic Center and Natasha Skin Center with 300 respondents. Data collection in this study was obtained through the distribution of questionnaires. The sampling method used in this research is purposive sampling. The results of the study found that Brand image has a positive and significant effect on customer loyalty, Customer experience has a positive and significant influence on customer loyalty, Vanity seeking has a positive and significant effect on customer loyalty, Materialism has a positive and significant influence on customer loyalty. , and Customer loyalty has a positive and significant influence on repurchase intention at the Larissa Aestehtic Center and Natasaha Skin Center beauty clinic services. Keywords: Brand Image, Customer Experience, Vanity Seeking, Materilism, Customer Loyalty, Repurchase Intention